The Principle of Non-Intervention in the Age of Humanitarian Crises - Marah, Thomas Sheku (Universitas Muhammadiyah Surakarta, 2025)
This research critically describes the evolving tension between the principle of non-intervention and the newly arising norm of the Responsibility to Protect (R2P) under international law. While state sovereignty has long been considered the pillar of the international order, increasing numbers of mass atrocities and humanitarian crises have prompted international actors to reassess their obligation to intervene where states fail to protect their citizens. This study undertakes a doctrinal and qualitative analysis of significant international legal instruments, case studies such as Libya and Syria, and scholarly writings to ascertain the normative and legal validity of humanitarian intervention and R2P. It analyzes the legal basis of the principle of non-intervention, the ethical grounds for humanitarian intervention, and the practical application of R2P through international organizations such as the United Nations. The research also explores the issue of operationalizing R2P, including selectivity, political manipulation, and inconsistency in state practice. The research demonstrates that while R2P offers an attractive normative framework for responding to mass atrocities, its enforcement is thwarted by geopolitical interests and the lack of binding legal status. The findings of the research demonstrate a clear need for reform of the international legal system and a more robust institutional commitment to balancing state sovereignty with humanitarian obligations, thereby conducting interventions within a legal, consistent, and accountable framework.